Estimating the positive predictive value of opportunistic population testing for gonorrhoea as part of the English Chlamydia Screening Programme. (March 2013) - Fowler, T; Edeghere, O; Inglis, N; Bradshaw, S
Advances in technology have raised the possibility of including gonorrhoea testing as part of chlamydia screening. In England this is recommended only where the positive predictive value (PPV) of the test is >90%. This study assessed the PPV for gonorrhoea testing using routine testing data. Routine data (including gonorrhoea testing) from the Greater Manchester Chlamydia Screening Programme (GMCSP) in 2009/2010, were used to estimate the PPV for gonorrhoea testing. Of those screened, 0.3% (59/18044) of men and 0.4% (174/41873) of women tested positive for gonorrhoea. The PPV was 82.3% in women and 73.6% in men, in those who also tested positive for chlamydia. For women and men testing negative for chlamydia the PPV for a positive gonorrhoea test was incalculable. The low PPV observed in most groups suggests that where population testing for gonorrhoea occurs there is a need for further confirmatory testing of positive results before treatment decisions are made. Clinicians should be aware of screening test result limitations in this context.